The concept of "Superman" in the Riau community’s pantun: Overview of anthropology metaphysics - Tri Tarwiyani,; Misnal Munir,; Sonjoruri Budiani Trisakti, (Technium Social Sciences Journal, 2020)
Pantun is one of the traditional literary works of the Riau Malay community. Pantun is even identified with the Malay community itself. Various values and teachings are contained in Pantun. However, these values have not been fully revealed. On the other side, there are so many concepts of superior from philosophers but the concept of superman originating from the viewpoint of a group or society is still few. Therefore, to enrich the view of superman, this article tries to formulate the concept of the manusia bertuah. This article came to the conclusion that the manusia bertuah in the Riau Malay community conception formulated based on the Riau Malay community Pantun are bermaruah who are berbudi and always keep malu, tahu diri, and tolak angsur or tolerance by upholding the syarak, customs, and resam of Malay.